Association of multiple blood metals with thyroid function in general adults: A cross−sectional study - Ye, Yanshi; Li, Ye; Ma, Qintao; Li, Ying; Zeng, Huixian; Luo, Yaosheng; Liang, Yongqian; Liu, Lan; Liu, Lingling; Lin, Xu; Yu, Genfeng; Song, Cheng; et al. (Frontiers in Endocrinology, 2023)
Introduction Thyroid function has a large impact on humans’ metabolism and is affected by iodine levels, but there is a scarcity of studies that elucidate the association between thyroid function and other elements. Methods We performed a cross-sectional study on 1,067 adults to evaluate the associations of the common essential metals with thyroid function in adults living in an iodine-adequate area of China. Serum free thyroxine (FT4), free triiodothyronine (FT3), thyroid stimulating hormone (TSH), and blood metals (zinc, iron, copper, magnesium, manganese, and calcium) were measured. Further, the thyroid hormone sensitivity indexes, FT3:FT4 ratio, and thyrotropin T4 resistance index (TT4RI) were calculated. Linear regression, quantile g-computation, and Bayesian kernel machine regression methods were used to explore the association of metals with thyroid function. Results We found that the TSH levels correlated with copper (negative) and zinc (positive). Iron and copper were positively associated with FT3 and FT4 levels, respectively. Iron (positive) and copper (negative) were correlated with the FT3:FT4 ratio. Furthermore, we found that manganese was inversely correlated with TT4RI, while zinc was positively correlated. Discussion Our findings suggest that manganese, iron, copper, and zinc levels were strongly correlated with thyroid function, and patients with thyroid disorders are recommended to measure those metals levels.